2009
DOI: 10.1189/jlb.0608354
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase (PDI) associates with NADPH oxidase and is required for phagocytosis of Leishmania chagasi promastigotes by macrophages

Abstract: PDI, a redox chaperone, is involved in host cell uptake of bacteria/viruses, phagosome formation, and vascular NADPH oxidase regulation. PDI involvement in phagocyte infection by parasites has been poorly explored. Here, we investigated the role of PDI in in vitro infection of J774 macrophages by amastigote and promastigote forms of the protozoan Leishmania chagasi and assessed whether PDI associates with the macrophage NADPH oxidase complex. Promastigote but not amastigote phagocytosis was inhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 54 publications
6
81
0
4
Order By: Relevance
“…However, pathways that adjust Nox activation to specific physiologic programs in cells are unclear. Our group has provided evidence that the endoplasmic reticulum (ER) redox chaperone protein disulfide isomerase (PDI) functionally regulates NADPH oxidase and associates with its subunits in distinct cell types (7)(8)(9)(10). PDI is the founding member of a large protein family belonging to the thioredoxin superfamily of dithiol-disulfide oxidoreductases, displaying thiol isomerase, oxidase, and reductase activities (11)(12)(13)(14).…”
Section: Vascular Smooth Muscle Cell (Vsmc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, pathways that adjust Nox activation to specific physiologic programs in cells are unclear. Our group has provided evidence that the endoplasmic reticulum (ER) redox chaperone protein disulfide isomerase (PDI) functionally regulates NADPH oxidase and associates with its subunits in distinct cell types (7)(8)(9)(10). PDI is the founding member of a large protein family belonging to the thioredoxin superfamily of dithiol-disulfide oxidoreductases, displaying thiol isomerase, oxidase, and reductase activities (11)(12)(13)(14).…”
Section: Vascular Smooth Muscle Cell (Vsmc)mentioning
confidence: 99%
“…Contrarily, induced PDI overexpression promotes preemptive spontaneous ROS generation, NADPH oxidase activity, and Nox1, but not Nox4 mRNA expression (8). In J-774 macrophages, PDI overexpression increases, whereas PDI silencing decreases Leishmania chagasi phagocytosis and NADPH oxidase activation (9). Moreover, we recently showed PDI requirement for activation of neutrophil NADPH oxidase, in both cell-free and whole cell systems (7).…”
Section: Vascular Smooth Muscle Cell (Vsmc)mentioning
confidence: 99%
“…This suggests that the oxidative stress induced by NADPH oxidase activation may have a favorable effect, instead of the expected anti-microbial effect, with regard to parasite infectivity. Recently, PDI has been shown to be involved in phagocytosis of Leishmania chagasi through regulation of NADPH oxidase, in which PDI was found to closely associate with the NADPH oxidase, and inhibitors of PDI (bacitracin, phenylarsine oxide, anti-PDI antibody) significantly blocked promastigote phagocytosis (40). These results correlate well with, and are supported by, the previous findings that proteomic study of macrophages showed that PDI is involved in the formation of the phagosomes during phagocytosis of some parasites, including Leishmania (66,81).…”
Section: Pdi Nadph Oxidase and Leishmania Entrymentioning
confidence: 99%
“…diphtheria toxin [29][30][31][32][33], cholera toxin [34], botulinum neurotoxins [35,36], anthrax toxin [37]) are apparently dependent on the redox states (either reduced or oxidized) of the specific disulfides of either the toxin molecules, or the host receptors. At the same time, protein disulfide isomerase (PDI) [38] and other redox factors, such as gamma-interferoninducible lysosomal thiol reductase (GILT) [39]) and NADPH oxidase [40][41][42], have been implicated in regulating the redox states of the disulfides. Similarly, PDI and others are also involved in the entry of numerous pathogenic bacteria (e.g.…”
Section: Disulfide Bond: a Redox-controlled Switch For Pathogen And Tmentioning
confidence: 99%
See 1 more Smart Citation